46th AIAA Fluid Dynamics Conference 2016
DOI: 10.2514/6.2016-4260
|View full text |Cite
|
Sign up to set email alerts
|

Linear Frequency Domain Reduced Order Modelling of Aerofoil Gust Response

Abstract: A method for constructing reduced order models of an aerofoil subject to gusts is presented. The method is based on subspace system identification in the frequency domain in order to obtain a model which retains the dynamic information of the original system, while having a comparatively smaller dimension. The gust is prescribed through the domain using the split velocity method to obtain the system frequency response. This is used to find the state matrices of the reduced system. By prescribing a series of 1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…They demonstrated that a well functioning load alleviation system needs to have a control surface on the outer wing and one on the inner wing so that essential parts of the load distribution of the wing-span can be influenced by the control system. Bagheri, Jones and Gaitonde [5] developed a model to predict gust responses using a reduced model of the LFD solver and could show that, for a series of 1-cosine gusts, their model proved a good agreement with the original system. Comparisons between LFD results and Double Lattice Methods (DLM) for gust encounter simulations on the NASA Common Research Model (CRM) were done by Kaiser, Friedewald and Nitzsche [6] and showed good results in terms of time savings and accuracy for applications in the linear gust regions.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that a well functioning load alleviation system needs to have a control surface on the outer wing and one on the inner wing so that essential parts of the load distribution of the wing-span can be influenced by the control system. Bagheri, Jones and Gaitonde [5] developed a model to predict gust responses using a reduced model of the LFD solver and could show that, for a series of 1-cosine gusts, their model proved a good agreement with the original system. Comparisons between LFD results and Double Lattice Methods (DLM) for gust encounter simulations on the NASA Common Research Model (CRM) were done by Kaiser, Friedewald and Nitzsche [6] and showed good results in terms of time savings and accuracy for applications in the linear gust regions.…”
Section: Introductionmentioning
confidence: 99%